Corporate governance of financial institutions - Hamid Mehran; Lindsay Mollineaux (Federal Reserve Bank of New York, 2012)
We identify the tension created by the dual demands of financial institutions to be value-maximizing entities that also serve the public interest. We highlight the importance of information in addressing the public's desire for banks to be safe yet innovative. Regulators can choose several approaches to increase market discipline and information production. First, they can mandate information production outside of markets through increased regulatory disclosure. Second, they can directly motivate potential producers of information by changing their incentives. Traditional approaches to bank governance may interfere with the information content of prices. Thus, the lack of transparency in the banking industry may be a symptom rather than the primary cause of bad governance. We provide the examples of compensation and resolution. Reforms that promote the quality of security prices through information production can improve the governance of financial institutions. Future research is needed to examine the interactions between disclosure, information, and governance.
Keywords: G01; G21; G32; G39; 330; financial institutions; governance; disclosure; information; market discipline; financial crisis